JURNALISME BENCANA DAN RANGSANGAN EMOSIONAL STUDI HUBUNGAN JURNALISME BENCANA BANJIR SURAT KABAR SOLOPOS DENGAN RANGSANGAN EMOSIONAL MAHASISWA UNIVET BANTARA SUKOHARJO - Gama, Betty (Scriptura, 2009)
Disaster journalism is aimed as how the media tells the disaster itself. Based on the data analysis toward the five (5) research variables, only the proximity variable that doesn’t have relation to the university students emotional stimulus, with the significance score of 0.864 > 0,005. Timeliness variable to the learners emotional stimulus with the significance score of 0.026 < 0.005. Consequence variable toward the leaners emotional stimulus with significance score of 0.000 < 0.005, human interest variable towards the learners emotional stimulus with significance score of 0.000 < 0.005 and magnitude variable toward learners emotional stimulus with significance score of 0.000 < 0.005. Testing data is using correlation Tata Jenjang Spearmens (rs) / Spearmans Phase Order with 5 % of trutworthiness. The sample of the research is the students at even semester of Veteran Bangun Nusantara University of Sukoharjo at academic year of 2007/2008 covering 98 students. Sampling technique which use is Proposional Simple Random Sampling.